Comprehensive evaluation of environmental availability, pollution level and leaching heavy metals behavior in non-ferrous metal tailings. (15th July 2021) - Jiang, Lei; Sun, Hongjuan; Peng, Tongjiang; Ding, Wenjin; Liu, Bo; Liu, Quan
Abstract: Amounts of abandoned non-ferrous metal tailings(NMT) piled in the open air are released under geochemistry and migrated to the surrounding environment, causing severe harm to the environment and human health. It is essential to evaluate the heavy metal pollution of NMT. In this study, R A C, I g e o, E F, and R I were used to evaluate the heavy metal pollution risk of NMT. To uniformly simplify the four evaluation results into a comprehensive evaluation result that can reflect the degree of heavy metal pollution risk. Assuming heavy metals' concentration, occurrence, and mobility make the same contribution to the degree of heavy metal pollution. Score the above four evaluation results according to the pollution level, and then weigh the scores to obtain a complete integral result: C R S Mo (17) > C R S Cd (13) > C R S Pb (11) > C R S Sr (8) > C R S Mn (7) > C R S Cu (5) > C R S Ni (4) > C R S Cr (3) = C R S Zn (3). Five higher risk heavy metal elements Mo, Cd, Pb, Sr, and Mn, were found. Cu, Ni, Cr, and Zn are at lower risk. The results showed that Mo, Mn, and Sr's evaluation is more accurate. Pb and Cd have not reached the detection limit for the time being, indicating that the release of heavy metal elements in tailings is not only related to the total concentration, occurrence state, and mobility of heavy metals but also affected by the pH of the tailings. This study's most significant finding is to propose a comprehensive integration result of pollution risk levels based on R A C, I g e o, E F, and R I as the comprehensive evaluation result of heavy metal pollution risk. Simultaneously, this research is also a valuable supplement to the existing risk assessment of heavy metal pollution. Graphical abstract: Image 1 Highlights: The contents of Pb, Zn, Cu, Ni, Cr, Cd, Mn, Mo, Sr exceed the background value. The comprehensive pollution risk score is Mo> Cd> Pb> Sr> Mn> Cu> Ni> Cr = Zn. The weak alkalinity of the tailings can maintain the stability of heavy metals. Mn and Mo' release in tailings is tiny with large stock, and the risk is still huge. Both the total amount and the release capacity of heavy metals should be considered.